The Environmental Impact of Etelebou Flow Station In Surface Water of Gbarain, Bayelsa State, Nigeria - I. Seiyaboh, Enetimi; C.N Angaye, Tariwari (Journal of Plant and Animal Ecology, 2018)
Environmental impact of anthropogenic activities from industrial sources, have become a threat to biodiversity. Water samples were collected from rivers around the flow station, and analysed from some physicochemical parameters and hydrocarbon contents. Result of the physicochemistry was reported for: pH (6.58± 0.04 - 6.76±0.01), conductivity (168.30±13.98 - 194.57±3.78 µS/cm), conductivity 8.29±0.04 - 10.66±0.02 NTU, salinity (0.07±0.00 - 0.09± 0.00 mg/l), and Total Solids (83.96±1.49 - 103.66±0.60mg/l). Other elemental analysis includes: sulphates (2.43±0.01 - 4.28 ±0.02 mg/l), nitrates (0.19±0.01 - 0.28±0.01 mg/l), carbonates (1.14±0.07 - 2.06±0.07 mg/l), calcium (8.45±0.10 - 11.70±0.25 mg/l), magnesium (1.14±0.07 - 2.56±0.03 mg/l), and sodium (4.37±0.15 - 5.62±0.03 mg/l). The values of THC and TPH were 0.92±0.08 - 1.51±0.03, and 0.37±0.13 - 0.76±0.07 mg/l respectively. Generally, the result indicated mild level of contamination in terms of Hydrocarbon contents. However, diagnostic data emerging for physicochemistry and some elemental property indicates the water is unfit for consumption. Notwithstanding, the order on contamination were reported as; downstream > midstream > upstream. Therefore this study concludes that there should be frequent monitoring of the recipient water bodies associated with the flow station in order to check anthropogenic activities, and conserve biodiversity.
Keywords: Hydrocarbon; Recipient water; Environmental Impact; Pollution.